Pengaruh Penambahan Co-solvent Metil Ester dan Waktu Reaksi pada Proses Transesterifikasi Minyak Kelapa Sawit Menjadi FAME (Fatty Acid Methyl Esters) - Daryono, Elvianto Dwi; Mustiadi, Lalu (Jurnal Teknik Kimia USU, 2022)
Biodiesel is a renewable energy that is expected to replace diesel. The process of making biodiesel is constrained due to the limited solubility of the reactants. One way to increase the solubility is to add a co-solvent that can dissolve polar and non-polar materials. Methyl ester is the best co-solvent because it is cheap and can shorten the stages of the biodiesel manufacturing process. The aim of the research was to obtain the optimum conditions for the transesterification process with the addition of co-solvent methyl ester. The operating conditions of the study were palm oil raw material, 1% NaOH catalyst mass, oil : methanol molar ratio = 1:6, stirring speed 100 rpm, reaction temperature 70 â°C, reaction time (5 minutes, 10 minutes, 15 minutes, 20 minutes, 25 minutes, 30 minutes) and the mass of co-solvent (0%, 5%, 10%, 15%). The optimum conditions of the study obtained the optimum FAME yield of 57.33% in the transesterification reaction of palm oil with 15% co-solvent methyl ester at a reaction time of 15 minutes. At the optimum condition obtained FAME concentration of 96.63% which meets SNI 7182-2015.